Upper Silurian (Gorstian, Ludfordian, PŘÍDOLÍ) Graptolite Biozonation in the Muhurr area (Albania) - Pashko, Pandeli llazar (Bulletin of the Geological Society of Greece, 2020)
Three stratigraphical sections and several outcrops through the upper Silurian graptolite shales of the Muhurr area, Albania have been revised. Based on a new detailed re-examination and re-evaluation of graptolite collections and previously unpublished and published studies, a biozonal scheme with much new biostratigraphical data is established. The graptolite assemblages are dominated by Monograptidae: Neodiversograptus, Saetograptus, Bohemograptus, Colonograptus, Pseudomonoclimacis and Lobograptus which are associated with several Retiolitidae. A total of 37 graptolite species has been identified; selected important species are illustrated. The present study recognized and defined the following seven upper Silurian graptolite biozones: nilssoni and scanicus-chimaera in the Gorstian Stage, leintwardinensis, tenuis and formosus in the Ludfordian Stage and parultimus-ultimus and perneri in the Přídolí Series.